Four new species of Eugenia (Myrtaceae) from the Caatinga and Atlantic Forest of northeastern Brazil - Coutinho, Karoline; Oliveira, Marla Ibrahim Uehbe De; Funch, Ligia Silveira (Phytotaxa, 2015)
There are described, illustrated and compared to similar taxa Eugenia caatingicola, E. funchiana, E. coccinea and E. potiraguensis. The first three species occur in areas of caatinga (dryland) vegetation (Bahia and Piauí states),while E. potiraguensis is encountered in the Atlantic Forest (Bahia), Brazil. Eugenia caatingicola can be distinguished from Eugenia subreticula by the texture of the periderm of the older branches, leaf apices retuse, and hypanthium sericeous. Eugenia funchiana is similar to E.dentata, but have undulate leaves, smaller petioles and pedicels, and hypanthium not costate. Eugenia coccinea differs from E. duarteana by having membranaceous leaves, calyx lobes with reddish trichomes at apex, and hypanthium glabrous. Eugenia potiraguensis differs from E. plicata by having central veins glabrous, larger petioles, and calyx lobes equal between them. Additionally, each species is evaluated in its conservation status.